2013
DOI: 10.1267/ahc.13015
|View full text |Cite
|
Sign up to set email alerts
|

Reassembly of Anterior Pituitary Organization by Hanging Drop Three-Dimensional Cell Culture

Abstract: The anterior pituitary gland comprises 5 types of hormone-producing cells and non-endocrine cells, such as folliculostellate (FS) cells. The cells form a lobular structure surrounded by extracellular matrix (ECM) but are not randomly distributed in each lobule; hormone-producing cells have affinities for specific cell types (topographic affinity), and FS cells form a homotypic meshwork. To determine whether this cell and ECM organization can be reproduced in vitro, we developed a 3-dimensional (3D) model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The cells were cultured for 5 days and processed for each experiment. We previously confirmed that an in vivo -like FS cell meshwork and filamentous laminin were formed 5 days after plating [ 21 ]. Cell aggregates were observed on an IX71 inverted fluorescence microscope (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…The cells were cultured for 5 days and processed for each experiment. We previously confirmed that an in vivo -like FS cell meshwork and filamentous laminin were formed 5 days after plating [ 21 ]. Cell aggregates were observed on an IX71 inverted fluorescence microscope (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 60%
“…GFP-positive and GFP-negative cells were mixed at a proportion of 0%, 5%, 10%, or 20% FS cells (a 5% proportion of FS cells is equivalent to that in normal adult rat anterior pituitary [ 4 ]). The hanging drop method was used for 3D culture, as described previously [ 21 ]. The cells were cultured for 5 days and processed for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Hanging drop 3D cell culture using anterior pituitary cells from Wistar rats was performed according to the protocol described previously by Tsukada et al [27]. A 25-μl drop containing 5,000 anterior pituitary cells was placed on the undersurface of 100-mm Petri dish lids, which were then cultured over sterile PBS at 37°C in a humidified incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these findings may suggest that fibromodulin, TGFβ2, and collagen regulation are interconnected in anterior pituitary gland. In this study, we investigated whether TGFβ signaling is associated with fibromodulin expression in folliculostellate cells and pericytes by using in situ hybridization for TGFβ receptor, immunocytochemistry for intracellular signal transduction in a monolayer culture of anterior pituitary cells, and a three-dimensional (3D) cell culture method that was successfully developed for our recent study [27]. …”
Section: Introductionmentioning
confidence: 99%
“…Obtaining human tissue is not feasible for routine testing, but the field of stem cell research promises interesting future approaches. layered 3D cortical tissue has already been generated (lancaster et al, 2013), and approaches to form 3D retinal tissue or adrenal tissue have also been described (Jin et al, 2011;Nistor et al, 2010;tsukada et al, 2013).…”
Section: Issues and Future Challenges To Be Addressed By 3d In Vitro mentioning
confidence: 99%